Polarity dependent strongly inhomogeneous In-incorporation in GaN nanocolumns. (25th July 2016) - Oppo, C I; Malindretos, J; Zamani, R R; Broxtermann, D; Segura-Ruiz, J; Martinez-Criado, G; Ricci, P C; Rizzi, A
Abstract: In this work, GaN/InGaN/GaN nanocolumns (NCs) have been grown by molecular beam epitaxy. Selective area growth (SAG) and self-organized growth (SOG) were performed simultaneously in patterned and unpatterned regions of the same substrate, respectively. The resulting structures show different tip morphologies and structural properties due to the different polarity along the growth direction, namely Ga-polar with r -plane faceted tips for the SAG NCs and N-polar with c -plane top facet for the SOG ones. When growing Ga-polar GaN/InGaN NCs, no indium is incorporated at a substrate temperature of T S = 700 °C. Rather, indium incorporation takes place under the same growth conditions on the N-polar NCs. The In-incorporation is investigated by means of nano x-ray fluorescence and diffraction, high-angle annular dark-field scanning transmission electron microscopy and high-resolution transmission electron microscopy.